Criminal policy and Criminal law: ultima ratio and the voluntary termination of pregnancy (abortion) (2020)
This text analyzes the historical, legal and criminal policy conditions that have justified the criminalization of abortion, in order to propose its relative decriminalization in the Colombian Penal Code of 2000. The central argument states that the crime of abortion, despite the fact that seeks to protect the dependent life of the unborn, in some cases it represents an excess of punitive intervention with respect to the constitutional rights of women, since the standards derived from the postulate of ultima ratio are not met to justify their proportionate restriction, effective and preventive. The rights of women and the life of the unborn can be adequately regulated, implementing a system of deadlines in addition to the conditions established by the Constitutional Court that protects them both. It is, without a doubt, a deep and difficult debate that raises serious political-criminal debates.